1988
DOI: 10.1136/bjsm.22.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and estimated energy expenditure during ballroom dancing.

Abstract: Ten competitive ballroom dance couples performed simulated competitive sequences of Modern and Latin American dance. Heart rate was telemetered during the dance sequences and related to direct measures of oxygen uptake and heart rate obtained while walking on a treadmill. Linear regression was employed to estimate gross and net energy expenditures of the dance sequences. A multivariate analysis of variance with repeated measures on the dance factor was applied to the data to test for interaction and main effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 13 publications
2
50
3
Order By: Relevance
“…Similar problem of inadequate preparation of athletes for making efforts in other dance areas was pointed out by Wyon and Redding [25], and Guidetti et al [22]. Also Blanksby and Reidy [9], as a result of the obtained data, put special emphasis on the importance of the physical preparation of dancers, although their values of individual indicators during dance were lower than those measured in this work.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Similar problem of inadequate preparation of athletes for making efforts in other dance areas was pointed out by Wyon and Redding [25], and Guidetti et al [22]. Also Blanksby and Reidy [9], as a result of the obtained data, put special emphasis on the importance of the physical preparation of dancers, although their values of individual indicators during dance were lower than those measured in this work.…”
Section: Discussionmentioning
confidence: 47%
“…In turn, Bria et al [19] showed that the greatest loads, expressed in energy expenditure in the group of men dancing in standard style, were observed in the middle of the round, in Viennese waltz. Other researchers reached similar conclusions in their papers, also classifying sports dance as a very heavy physical activity [8,9].…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In contrast, in a later study, Liiv et al (9) found that BD was more intensive for the female partner. Furthermore, in an early study, females tended to achieve higher heart rates in all of the five dances (2). The discrepancy and the magnitude of differences between genders in these studies may result from differences in competitors' level, or from using different experimental settings and intensity indicators.…”
Section: Introductionmentioning
confidence: 99%